The impact of foreign currency derivatives on firm market value: Evidence from Finland in the 2007–2012 financial crisis - Leppänen, Salla (My University, 2013)
This study examines the impact of foreign currency derivatives use on firm market value and stock returns during the financial crisis 2007–2012. The sample consists of nonfinancial firms listed in Nasdaq OMX Helsinki. Thus, the focus of the study is in Finland during a specific and extreme market period. During a financial crisis the predictability of market is even more uncertain and market movements can be enormous. It causes a significant risk in the foreign currency market and a greater need for firms to hedge their currency positions than during a stable market condition. The effects of foreign currency derivatives use may be stronger than found earlier because Finnish firms have more foreign operations than widely studied U.S. firms, and an instable period of financial crisis can multiply the effects of foreign currency hedges. Firm market value is measured by Tobin’s Q. The association between foreign currency derivatives and Tobin’s Q is examined with mean and median tests, and univariate and multivariate regressions. The multivariate regression, which includes control variables, is estimated using both pooled OLS and fixed effects regressions. Similar methodology is used to detect the association between foreign currency derivatives and stock returns. Foreign currency derivatives use is associated with significantly greater market value in a sample of firms without foreign sales. These are exposed to foreign currency risk through import and export competition although they do not have a direct foreign currency exposure. Generally, mean and median tests and some regressions indicate that foreign currency derivatives are associated with lower Tobin’s Q during the financial crisis. Contrary, the association between foreign currency derivatives and stock returns is mainly positive but insignificant implying that foreign currency derivatives use does not affect stock returns. However, the fit of these models remains relatively low.
Keywords: foreign currency derivatives; hedging; risk management; firm value; financial crisis; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|